Implementation of the Brown–Robinson method for solving zero-sum matrix games - Liubomir CHIRIAC; Natalia JOSU (Acta et Commentationes, Sciences of Education, 2025)
This article examines the implementation of the Brown–Robinson method for solving zero-sum matrix games. It presents the theoretical foundations of the method and describes the iterative algorithm employed in this context. A practical example illustrates the step-by-step application of the method and highlights the significance of the results obtained. The study emphasizes the method’s effectiveness in identifying optimal strategies and its relevance within game theory.